2019
DOI: 10.1002/mawe.201900074
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characterisation of the shear, bending and friction behaviour of bindered woven fabrics during the forming process

Abstract: A critical process step within the liquid composite moulding constitutes in the preforming of two‐dimensional textile material into a near‐net‐shape and load‐capable fibre structure by stamp forming. This paper presents fundamental material experiments on the shearing behaviour, bending properties and friction behaviour considering the binder quantity and forming temperature. In addition, the influence of the process time on the resulting stability of the preform is examined. The findings indicate that the qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
2
6
1
Order By: Relevance
“…At 105 C and above, the swirl fiber starts breaking and forming drops, leading to an uneven spray pattern. This observation is consistent with the data sheet of CeTePox AM1010 [45] which recommends temperatures between 90 and 95 C for a uniform swirl spray application and observations of Marla et al [46] A possible explanation for the knots is given in Formoso et al [45]. It was shown that increasing the ratio between spray airflow and material flow increases the risk of the swirl making contact with itself and forming knots.…”
Section: Binder Viscosity and Sprayabilitysupporting
confidence: 89%
See 2 more Smart Citations
“…At 105 C and above, the swirl fiber starts breaking and forming drops, leading to an uneven spray pattern. This observation is consistent with the data sheet of CeTePox AM1010 [45] which recommends temperatures between 90 and 95 C for a uniform swirl spray application and observations of Marla et al [46] A possible explanation for the knots is given in Formoso et al [45]. It was shown that increasing the ratio between spray airflow and material flow increases the risk of the swirl making contact with itself and forming knots.…”
Section: Binder Viscosity and Sprayabilitysupporting
confidence: 89%
“…After releasing the flexural force, the samples stay in their deformed shape but slowly return to their initial state. The measured flexural modulus is also lower than the ones found in Dickert [24] and Coutandin et al [46] for powder binders, while the flexural stress reaches similar values when using a test speed of 60 mm/min. In both publications, the initial flexural modulus of the plain textile without binder is already higher (50 MPa for Dickert and 380 MPa for Coutandin et al) making it difficult to directly compare the results.…”
Section: Three-point Flexural Bendingcontrasting
confidence: 48%
See 1 more Smart Citation
“…The cantilever bending test of woven fabric composite was performed at different forming temperatures. The forming temperature has no significant influence on the bending modulus of the composite [114].…”
Section: Numerical Characterization Under Various Mechanical Loading ...mentioning
confidence: 94%
“…The mechanical behavior of bindered (EPIKOTE Resin 0539) and dry woven fabrics (SIGRATEX C W305-PL1/1), which has been examined under consideration of the forming temperature [ 86 ], showed, that binder quantity and forming temperature have a substantial impact on the in-plane shear behavior. When temperatures dropped, the impact of the binder and activation time increased.…”
Section: Influence Of Binders On Lcm Technologymentioning
confidence: 99%